Effect of drying temperature on Ti0₂ thin film by sol-gel method: article - Mat Rosli, Nurul Suhada (2014)
This paper represents the effect of drying temperature on Titanium Dioxide (Ti0₂) thin film. The Ti02 thin films were prepared on glass substrate by using sol-gel spin coating method. The thin films were dried at six different temperatures at room temperature, 50°C, 100°C, 150°C, 200°C, and 250°C. The sample was characterized into electrical, optical and structural properties. The I-V measurement was taken under illumination by using two point probes solar simulator (BUKOH KEIKI-EP2000). Based on the result obtained, the sample dried at 250°C shows the best in all characterizations. The resistivity decreased and conductivity increased with the increase of the temperature.